Mass culture of Japan (Journal of Oriental Studies, 2018)
This article is devoted to this phenomenon of recent decades as the mass culture of Japan. Nowadays,the Japanese mass culture, preserving its unique national characteristics, increasingly invades theworld cultural space and begins to form the style of a new generation in both the West and the Eastcountries. The article deals with such manifestations of Japanese mass culture as anime and manga,which have become Japan’s specialty all over the world. Also shown are various subcultures: suqueban,tekhnokozoku, yankee and bosozoku, kol, ganguro, manba, kigurumi, lolita, decora. In article paid moreattention to the trend of “kawaii”, the elements of which are found in Japan everywhere, in large companiesand in small shops, in the government and in municipal institutions.